2021
DOI: 10.3389/fimmu.2020.620784
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein-Based Strategy to Reduce Antibiotic Dosing for the Treatment of Pneumococcal Infection

Abstract: C-reactive protein (CRP) is a component of innate immunity. The concentration of CRP in serum increases in microbial infections including Streptococcus pneumoniae infection. Employing a mouse model of pneumococcal infection, it has been shown that passively administered human wild-type CRP protects mice against infection, provided that CRP is injected into mice within two hours of administering pneumococci. Engineered CRP (E-CRP) molecules have been reported recently; unlike wild-type CRP, passively administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Substantial evidence indicates that the synergistic action between existing antibiotics and bioactive compounds is a unique and promising concept [ 222 , 223 , 224 ]. A study found that oleanolic acid, when used in conjunction with erythromycin, gentamicin, ciprofloxacin, and norfloxacin, exhibited synergistic effects against Gram-negative bacterial strains, potentially aiding in antimicrobial therapy [ 225 ].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Substantial evidence indicates that the synergistic action between existing antibiotics and bioactive compounds is a unique and promising concept [ 222 , 223 , 224 ]. A study found that oleanolic acid, when used in conjunction with erythromycin, gentamicin, ciprofloxacin, and norfloxacin, exhibited synergistic effects against Gram-negative bacterial strains, potentially aiding in antimicrobial therapy [ 225 ].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…The physiological function of CRP is related to calcium-dependent ligand affinity ( 30 , 31 ). Many studies have used calcium-dependent PC affinity to successfully separate CRP from blood, such as horseshoe crab ( 32 ), mouse ( 33 ), dog ( 34 ), cat ( 35 ), cow ( 36 ), since the calcium-dependent PC affinity is conserved in the species and as a basis for testing the function of multi-species CRP in experiments.…”
Section: Crp Structure-related Featuresmentioning
confidence: 99%